Pengaruh Komitmen Organisasi, Gaya Kepemimpinan, dan Time Budget Pressure terhadap Kepuasan Kerja Auditor pada KAP di Makassar - Anwar, Azwar; Afiah, Nur (Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This study aims to determine the effect of organizational commitment, leadership style and time budget pressure on auditor job satisfaction at the Public Accounting Office in Makassar.. The method of determining the sample used is convenience sampling, which is a sampling technique with consideration of convenience. Data collection techniques were carried out by distributing questionnaires. The questionnaire in this study used a Likert scale as the measurement scale of the research instrument. Data analysis technique used multiple linear regression analysis and hypothesis test consisting of partial test (t test) and simultaneous test (f test). The analysis used in this study is quantitative analysis. The findings in this study indicate that the independent variable of organizational commitment (X1), leadership style (X2) and time budget pressure (X3) have a positive and significant effect on the dependent variable of auditor job satisfaction (Y), both testing partially (t-test) and testing simultaneously (F test).Keywords: organizational commitment, leadership style, time budget pressure and auditor job satisfaction